Strategi Penawaran dalam Industri Konstruksi (Studi Kasus di Layanan Pengadaan Secara Elektronik, Kota Bandung) - Hakas Prayuda, Mandiyo Priyo , (Universitas Muhammadiyah Yogyakarta, 2013)
The aims of this research are to calculate the value of mark-up using bidding strategy approach and to determine the best bidding strategy to win a tender with the optimum mark-up value and the optimum profit. The data being used in this research are auction data that have been completed in 2010-2012 at LPSE Bandung using statistical approach namely discrete multi distribution, normal multi distribution, and single normal distribution. Bidding strategy methods being used are Friedman Method, Gates Method, and Ackoff Sasieni Method. The Friedman Method can generate an optimum mark-up of 10% with expected profit of -0.0014, an optimum mark-up of -9% with expected profit of -0.0003, and an optimum mark-up of -1% with expected profit -0.0004 for discrete multi-distribution, multi-normal distribution, and single normal distribution, respectively. The Gates Methods can produce an optimum mark up of 6% with expected profit of 1,5000, an optimum mark up of 5% with expected profit 0.0097, and an optimum mark up of 6% with expected profit 1.2888 for discrete multi distribution, multi-normal distribution, and single normal distribution, respectively. While the Ackoff Sasieni Methods can generates an optimum mark-up of -2% with expected profit -0.0003, an optimum mark-up of 1% with expected profit for 0,0013 for discrete multi distribution, and for both multi and single normal distributions, respectively.